2005
DOI: 10.1111/j.1834-7819.2005.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

The dental implications of bisphosphonates and bone disease

Abstract: In 2002/2003 a number of patients presented to the South Australian Oral and Maxillofacial Surgery Unit with unusual non‐healing extraction wounds of the jaws. All were middle‐aged to elderly, medically compromised and on bisphosphonates for bone pathology. Review of the literature showed similar cases being reported in the North American oral and maxillofacial surgery literature. This paper reviews the role of bisphosphonates in the management of bone disease. There were 2.3 million prescriptions for bisphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 32 publications
(52 reference statements)
1
83
0
4
Order By: Relevance
“…The potentially catastrophic conse quences of developing established BON are such that we feel that general den tal practitioners should ask specifi cally about these drugs as part of their medi cal history for new patients and enquire again with returning patients. 20 The effects of bisphosphonates is known to last a long time with most cases of BON associated with oral bisphos phonates presenting after 36 months and most associated with parenteral bisphosphonates presenting after 13 months. Patients with a past history of bisphosphonate therapy should there fore be managed in the same manner as patients on current therapy.…”
Section: Gdp Knowledge Of Bisphosphonatesmentioning
confidence: 99%
“…The potentially catastrophic conse quences of developing established BON are such that we feel that general den tal practitioners should ask specifi cally about these drugs as part of their medi cal history for new patients and enquire again with returning patients. 20 The effects of bisphosphonates is known to last a long time with most cases of BON associated with oral bisphos phonates presenting after 36 months and most associated with parenteral bisphosphonates presenting after 13 months. Patients with a past history of bisphosphonate therapy should there fore be managed in the same manner as patients on current therapy.…”
Section: Gdp Knowledge Of Bisphosphonatesmentioning
confidence: 99%
“…32,33 For ZA-induced BRONJ in rats, no information is available on weight differences. In this study, the weight measurements prior to sacrificing showed that the rats of the Figure 3 Micrograph of the haematoxylin and eosin stained section showing (a) failure in healing of the bone in the extraction socket of a rat of the zoledronic acid (ZA) group (3100), (b) a small necrotic portion of the alveolar bone surrounding the extraction socket of a rat of the ZA 1 teriparatide group (3200).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are effective with clinical improvements recorded over decades. Annual costs are much more affordable than hormones and consequently are widely successfully and frequently prescribed for osteoporosis [37]. Health care workers managing OP patients should have OP cases mouth fully checked out and stabilized, preferably by a dental specialist, before prescribing BPT.…”
Section: Discussionmentioning
confidence: 99%
“…Femigel® is an example, Thrombus formation is the major concern when women take hormones for OP (22,36,37). Various forms of estrogen replacement are used, but are beyond the scope of this perspective.…”
Section: Calcitonin and Parathyroid Hormone (Pth)mentioning
confidence: 99%